Combined Reversed Phase HPLC, Mass Spectrometry, and NMR Spectroscopy for a Fast Separation and Efficient Identification of Phosphatidylcholines. (25th August 2010) - Willmann, Jan; Thiele, Herbert; Leibfritz, Dieter
Abstract : In respect of the manifold involvement of lipids in biochemical processes, the analysis of intact and underivatised lipids of body fluids as well as cell and tissue extracts is still a challenging task, if detailed molecular information is required. Therefore, the advantage of combined use of high-pressure liquid chromatography (HPLC), mass spectrometry (MS), and nuclear magnetic resonance (NMR) spectroscopy will be shown analyzing three different types of extracts of the ubiquitous membrane component phosphatidylcholine. At first, different reversed phase modifications were tested on phosphatidylcholines (PC) with the same effective carbon number (ECN) for their applicability in lipid analysis. The results were taken to improve the separation of three natural PC extract types and a new reversed phase (RP)-HPLC method was developed. The individual species were characterized by one- and two-dimensional NMR and positive or negative ion mode quadrupole time of flight (q-TOF)-MS as well as MS/MS techniques. Furthermore, ion suppression effects during electrospray ionisation (ESI), difficulties, limits, and advantages of the individual analytical techniques are addressed.